Training projects by competences in the professional training of students of the professional school of historical social and geographic sciences - UNHEVAL, Huánuco - Lugo-Villegas, Ido (2023)
The main objective was to determine the influence of the implementation of training projects by competencies in the professional training of students of the Professional School of Historical, Social and Geographical Sciences of UNHEVAL-Huánuco. In materials, the workbook, bibliographic information, and computer were used. The analytical-synthetic methods have served to particularize, integrate, and disintegrate the theoretical and empirical information during the interpretation of results and the discussion. The sample was 16 students of the IX Cycle. The data collection techniques were bibliographic analysis, documentary analysis and survey. The data collection instrument was the questionnaire. The statistics served for the descriptive and inferential analysis of the research results, through the use of the spreadsheet and SPSS. The general result reflects that the majority of the students surveyed perceive that the implementation of training projects by competences are satisfactory for their professional training (93.75%), and in the specific results, the perception of the implementation of training projects by competences , is satisfactory in the academic dimension (87.50%), in the research dimension (93.75%), in the social responsibility dimension (81.25%), in the cultural dimension (75.00%), and in the axiological dimension (81.25%). The main conclusion reflects that the implementation of training projects by competencies positively influences the professional academic training, research, social, cultural and axiological responsibility of the majority of the students of the Professional School of Historical, Social and Geographical Sciences of UNHEVAL.